Synthesis of furo[2,3-b]pyran-2-ones through Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols and alpha-ketoesters - Thorat, Sagar S.; Kataria, Priyanka; Kontham, Ravindar (Organic Letters, 2018)
Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols (5-hexyn-1-ol systems) with a-ketoesters involving a dual activation process (pi and sigma) has been developed for the first time. This reaction proceeds through cycloisomerization of alkynol to give the 6-endo-enol ether followed by annulation with an alpha-ketoester to furnish furo[2,3-b]pyran-2-ones in good yields. Chemical structures of all products were rigorously confirmed by single crystal X-ray analysis and analogy.

Studies directed toward the synthesis of hedycoropyrans: total synthesis of des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) - Kataria, Priyanka; Nomula, Rajesh; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2022)
A full account of our efforts directed towards the synthesis of the diarylheptanoid-derived natural products hedycoropyrans that led to the total synthesis of ent-rhoiptelol B is described. In this endeavor, we have attempted two distinct synthetic strategies to access hedycoropyrans A and B, which led us to establish a facile synthetic route for des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) from simple and readily accessible building blocks of 4-allylanisole and vanillin, employing Sharpless asymmetric epoxidation, CBS reduction, and an intramolecular AgOTf-catalyzed oxa-Michael reaction of suitably functionalized hydroxy-ynone as key transformations. The investigations disclosed herein will provide insights into designing novel synthetic routes for THP-DAH-derived natural products.

Bi(III)-catalyzed synthesis of substituted furans from hydroxy-oxetanyl ketones: application to unified total synthesis of shikonofurans J, D, E, and C - Kataria, Priyanka; Sahoo, Shubhranshu Shekhar; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
We report an improved synthetic protocol for hydroxymethyl-derivedpolysubstituted furans employing Bi-(III)-catalyzed dehydrative cycloisomerizationof alpha-hydroxy oxetanyl ketones. This procedure provides rapidaccess (within 5 min) to highly substituted furans with exceptionalfunctional group diversity, excellent yields, generality, scalability,and operationally simple reaction conditions. Further, it demonstratedthe utility of this method in the first enantioselective total synthesisof furyl-hydroquinone-derived biologically potent natural productsshikonofurans J, D, E, and C in seven linear steps, starting fromreadily available building blocks of 2,5-dihydroxy acetophenone and3-oxetanone employing chiral-phosphoric acid (TRIP)-catalyzed asymmetricprenylation as a key step to induce the chirality.

Concise and collective total syntheses of 2,4-disubstituted furan-derived natural products from hydroxyoxetanyl ketones - Sahoo, Shubhranshu Shekhar; Kataria, Priyanka; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
The furan moiety, prevalent in bioactive natural products and essential drugs, presents intriguing structural features that have spurred our exploration into streamlined chemical synthesis routes for related natural products. In this study, we demonstrate the concise total synthesis of eight 2,4-disubstituted furan-derived natural products (including methylfuroic acid, rabdoketones A and B, paleofurans A and B, tournefolin C, and shikonofurans A and B). Our methodology revolves around the utilization of hydroxyoxetanyl ketones as pivotal intermediates. The approach encompasses transformations such as selective organo-catalyzed cross-ketol addition, synthesis of hydroxymethyl-tethered furans through Bi(OTf)3 catalyzed dehydrative cycloisomerization of alpha-hydroxyoxetanyl ketones, and a hydrogen atom transfer (HAT)-mediated oxidation of primary alcohols into the corresponding acids. This comprehensive synthetic strategy highlights the versatility of hydroxyoxetanyl ketones as invaluable building blocks in the synthesis of furan-containing natural products. A unified total synthesis of eight 2,4-disubstituted furan-derived natural products has been achieved through Bi(iii)-catalyzed cascade cycloisomerization of alpha-hydroxyoxetanyl ketones and hydrogen atom transfer-mediated oxidation of primary alcohols as pivotal transformations.

Divergent access to polycyclic spiro- and fused-N,O-ketals through Bi(OTf)3-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines and alkynols - Nakate, Ashwini K.; Kataria, Priyanka; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2024)
Bismuth(iii) triflate-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines (derived from saccharin) and alkynyl alcohols (4-pentyn-1-ols and 5-hexyn-1-ols) has been reported. This cascade annulation provides a diverse array of polycyclic spiro-and-fused N,O-ketals with excellent substrate scope, good isolated yields, and diastereoselectivities under mild reaction conditions.

Novel prodrug-inspired eugenol derivatives with enhanced bioavailability, anti-diabetic and anti-glycation efficacies - Kataria, Priyanka; Vairale, Shiva; Mote, Chandrashekhar; Joshi, Kaustubh; Joshi, Rakesh; Kulkarni, Mahesh J.; Giri, Ashok P.; Kontham, Ravindar; Agawane, Sachin B. (Journal of Molecular Structure, 2026)
In this study, we present the design, synthesis, and evaluation of novel eugenol analogs aimed to overcome its limited bioavailability due to insolubility in aqueous media. Thus, we re-engineered eugenol using prodruginspired structural modifications to improve pharmacokinetic properties. First, we structurally modified eugenol and synthesized its natural amino acid conjugates as esters and carbamates. These were prepared in NBoc protected, free amine, and HCl salt forms. These modifications are expected to improve the polarity and solubility of eugenol congeners in biological systems. They can also release the parent eugenol through enzymatic hydrolysis, enhancing its therapeutic potential. Next, we comprehensively screened for these derivatives through in silico studies followed by in vitro and in vivo assays. These include DPPH radical scavenging (IC50 range: 37.7 to 103.7 mu M), inhibition of (i) alpha-amylase (IC50 23.1 to 67.3 mu M), (ii) alpha-glucosidase (IC50 43.6 to 50.4 mu M), (iii) glycation (IC50 31.9 to 110.3 mu M) along with pharmacokinetic profiling and toxicity assessments. These experiments collectively demonstrated improved activity of eugenol analogs for several important parameters. Specifically, six analogs-epoxy eugenol (39), hydroxy eugenol (43), aspartate eugenol (26), isoleucinate eugenol (24), glutamate eugenol (37), and glutamate-salt eugenol (27) exhibited superior bioavailability, absorption, and distribution over to the parent compound eugenol. These analogs were found to be non-toxic and safe for oral administration. Overall, the study establishes a mechanistic and rational framework for modifying eugenol to overcome its inherent biopharmaceutical limitations, positioning them as promising candidates for treating diabetes and glycation-related conditions.
Keywords: Amino acid conjugates; Antidiabetic activity; Bioavailability enhancement; Drug design and synthesis; Eugenol analogs; In silico and in vitro studies